From morphological to ecological adaptation of the cornea in Oxudercinae fishes - Hu, Wenxian; Mu, Yuan; Wei, Chuanyu; Gai, Yulin; Zhang, Jie (Frontiers in Marine Science, 2022)
The outer cornea plays an important role in animal adaptation and survival in different environments; however, research on the morphological and ecological adaptation of corneal structure is still rare in amphibious fish. In this study, scanning electron microscopy (SEM) was used to evaluate the microstructure and adaptation of corneal epithelial cells in Oxudercinae. The results showed that the corneas of Oxudercinae species possess microridges, microvilli, and microplicae, as well as different numbers of epithelial cells. The morphological structure of corneal epithelial cells also showed different adaptive characteristics for moving between water and land, observed by collecting samples and comparing the results with previous results. Further analyses showed that there were significant differences in epithelial cell density (F4, 22=5.436, P=0.003) and microridge width (F4, 22=8.392, P<0.001) among species with different levels of aquatic dependence. In addition, a significant negative correlation between epithelial cell density and microridge width and separation width was confirmed (P<0.05). Interestingly, a significant negative correlation between habitat type, cell density and microridge was uncovered, as well as a positive correlation between habitat type and separation width (P<0.05). The results indicated that the corneal structure of Oxudercinae species has adaptive characteristics to amphibious habitats.